Tetrahydrofurofuranoid Lignans, Eudesmin, Fargesin, Epimagnolin A, Magnolin, and Yangambin Inhibit UDP-Glucuronosyltransferase 1A1 and 1A3 Activities in Human Liver Microsomes - Ria Park; Eun Jeong Park; Yong-Yeon Cho; Joo Young Lee; Han Chang Kang; Im-Sook Song; Hye Suk Lee (MDPI AG, 2021)
Eudesmin, fargesin, epimagnolin A, magnolin, and yangambin are tetrahydrofurofuranoid lignans with various pharmacological activities found in Magnoliae Flos. The inhibition potencies of eudesmin, fargesin, epimagnolin A, magnolin, and yangambin on six major human uridine 5'-diphospho-glucuronosyltransferase (UGT) activities in human liver microsomes were evaluated using liquid chromatography-tandem mass spectrometry and cocktail substrates. Eudesmin, fargesin, epimagnolin A, magnolin, and yangambin inhibited UGT1A1 and UGT1A3 activities, but showed negligible inhibition of UGT1A4, UGT16, UGT1A9, and UGT2B7 activities at 200 μM in pooled human liver microsomes. Moreover, eudesmin, fargesin, epimagnolin A, magnolin, and yangambin noncompetitively inhibited UGT1A1-catalyzed SN38 glucuronidation with Ki values of 25.7, 25.3, 3.6, 26.0, and 17.1 μM, respectively, based on kinetic analysis of UGT1A1 inhibition in pooled human liver microsomes. Conversely, the aforementioned tetrahydrofurofuranoid lignans competitively inhibited UGT1A3-catalyzed chenodeoxycholic acid 24-acyl-glucuronidation with 39.8, 24.3, 15.1, 37.6, and 66.8 μM, respectively in pooled human liver microsomes. These in vitro results suggest the necessity of evaluating whether the five tetrahydrofurofuranoid lignans can cause drug-drug interactions with UGT1A1 and UGT1A3 substrates in vivo.